Hubungan Pola Mendengarkan Siaran Konservasi Radio Edelweis dengan Sikap Khalayak terhadap Program Adopsi Pohon - Ayu Pratiwi; Hadiyanto Hadiyanto (Institut Pertanian Bogor, 2018)
There are many researches on community radio in Indonesia have become a special interest to know how community radio still exists among the middle class people. Community Radio is a medium capable of providing information to citizens in remote areas. Become a medium of information without any commercial side achieved. Community Radio can be enjoyed by all people, from teenager to adult. Do not see educational background, and job. Community Radio becomes a forum to support community empowerment programs conducted by the local government. Empowerment program in question is a program that aims to prosper and promote the community. Presented in simple benuk broadcaster Radio Community is able to present with simple language and equipped with entertainment